Task or time? Comparing methods for measuring the gender distribution of work - Banerjee, Archis; Kumar, Neha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2024)
There is growing evidence that gender disparities in the distribution of paid and unpaid work impose constraints on women’s well-being and livelihoods, reducing access to paid employment, and time for education, leisure, and social activities. Yet, gender disparities in unpaid work often go undiagnosed by traditional household surveys. While time-use surveys are well-suited for measuring unpaid work, they are often expensive to administer and take substantial amounts of survey time, leading to respondent fatigue, particularly in multi-topic surveys where other outcomes are also being collected.